Pengaruh Kualitas Layanan Elektronik dan Kepercayaan terhadap Loyalitas Pelanggan Shopee: Kepuasan Sebagai Variabel Mediasi - Fikri Farhan; Alif Muhammad Wiken Alamsyah Putra; Slamet (Akmenika: Jurnal Akuntansi dan Manajemen, 2025)
Shopee is the leading e-commerce platform in Indonesia in terms of user base. However, amid increasing competition and a declining trend in visitor numbers, maintaining customer loyalty has become a critical challenge. This study aims to examine the influence of electronic service quality and trust on customer loyalty, with satisfaction as a mediating variable. Data were collected through an online questionnaire distributed to 270 respondents in D.I. Yogyakarta who are active users of the Shopee application. The data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) technique, employing the SmartPLS 4.1.0.2 software. The findings reveal that both electronic service quality and trust have a positive effect on customer satisfaction. Trust and satisfaction also positively influence customer loyalty. However, electronic service quality does not have a direct effect on loyalty, but rather an indirect effect through satisfaction. These findings underscore the importance of building trust and ensuring customer satisfaction to sustain loyalty in the competitive e-commerce industry.